Elaboration and Evaluation of Contents about Hearing Health Inserted in Cybertutor - Corrêa, Camila de Castro; Silva, Ricelly Avila da; Blasca, Wanderléia Quinhoneiro (International Archives of Otorhinolaryngology, 2014)
Introduction Cybertutor (electronic tutor) is a type of information and communication technology to disseminate knowledge about hearing, aiming at the prevention of hearing alterations and, when needed, early treatment, in addition to social inclusion of the hearing impaired. However, it is important to evaluate the level of language used in the content and the subjective perception of the target public regarding improvements of the tool.Objective To improve content about hearing health inserted in a cybertutor and to evaluate the level of legibility and the quality of the content and material made available.Method For the construction of the content, text and audiovisual resources were used, based on scientific publications, and were evaluated objectively with Flesch Reading Ease test and subjectively with a questionnaire created by the authors and answered by 10 ninth-year pupils.Results Two modules on hearing health were created, “Hearing Health” and “Intervention and Rehabilitation,” which received Flesch scores of 50.8 and 51.4%, respectively, making it necessary to have a sixth- to ninth-year education to understand the material. The students' evaluation in reference to language and material showed that 55.5% considered the contents excellent; 38.2% classified the contents as satisfactory; 6.3% considered them reasonable; and 0% classified them as unsatisfactory.Conclusion The contents inserted in the cybertutor about hearing health presented a language level considered easy for the age group of the target population, in addition to receiving good subjective evaluation from the pupils, facilitating access to the information.
Keywords: hearing; speech; language and hearing sciences; education; distance; primary prevention; health education; information technologies and communication projects